Surface modification for bonding between amalgam and orthodontic brackets - Wittawat Wongsamut; Sirichom Satrawaha; Kornchanok Wayakanon (Wolters Kluwer Medknow Publications, 2017)
Objective: Testing of methods to enhance the shear bond strength (SBS) between orthodontic metal brackets and amalgam by sandblasting and different primers. Materials And Methods: Three hundred samples of amalgam restorations (KerrAlloy®) were prepared in self-cured acrylic blocks, polished, and divided into two groups: nonsandblasted and sandblasted. Each group was divided into five subgroups with different primers used in surface treatment methods, with a control group of bonded brackets on human mandibular incisors. Following the surface treatments, mandibular incisor brackets (Unitek®) were bonded on the amalgam with adhesive resin (Transbond XT®). The SBS of the samples was tested. The adhesive remnant index (ARI) and failure modes were then determined under a stereo-microscope. Two-way analysis of variance, Chi-square, and Kruskal-Wallis tests were performed to calculate the correlations between and among the SBS and ARI values, the failure modes, and surface roughness results. Results: There were statistically significant differences of SBS among the different adhesive primers and sandblasting methods (P < 0.05). The sandblasted amalgam with Assure Plus® showed the highest SBS (P < 0.001). Samples mainly showed an ARI score = 1 and mix-mode failure. There was a statistically significant difference of surface roughness between nonsandblasted amalgam and sandblasted amalgam (P < 0.05), but no significant differences among priming agents (P > 0.05). Conclusions: Using adhesive primers with sandblasting together effectively enhances the SBS between orthodontic metal brackets and amalgam. The two primers with the ingredient methacryloxydecyl dihydrogen phosphate (MDP) monomer, Alloy Primer® and Assure Plus®, were the most effective. Including sandblasting in the treatment is essential to achieve the bonding strength required.